Backgrounding of LGBT in Newspaper Coverage in Malaysia - Collin, Jerome; Ting, Su Hie; Audrea, Johnson (Asian Scholars Network (002903215-H), 2021)
In Malaysia, Lesbian, Gay, Bisexual dan Transgender (LGBT) face moral sanctions and legal challenges because it is prohibited by Islam and not condoned by major religions. A search using Google Trends show that there was a spike of interest on “LGBT in Malaysia” in 2009 and 2019, but there has been sustained interest since 2014. The present study examined framing of LGBT in four online newspapers in Malaysia. The specific objectives of the study were to determine the percentage of episodic and thematic framing in the newspapers, and to compare the topics that are reported in LGBT news. LGBT seems to be backgrounded in newspaper coverage by Astro Awani, Free Malaysia Today, Malaysiakini and The Star Online because only 60 articles published in 2019 were related to LGBT. The analysis showed that 81.67% of the articles were episodic frames and 18.33% were thematic frames. Malaysiakini had relatively more thematic articles while Astro Awani had the lowest percentage of thematic articles on LGBT. Over half (61.67%) of the articles were on LGBT news stories in Malaysia while other articles reported LGBT-linked persons or events in other countries. The local topics reported on LGBT were specific events which generated views on LGBT from politicians, religious leaders, and activists. The coverage of LGBT topics in other countries included criminalisation and societal discrimination of LGBT, and support for LGBT. The findings suggest caution in news on LBGT, with newspapers treading a thin line between affirming human rights and taking the official position of the country on LGBT.